EFEKTIVITAS MEDIA PENYULUHAN BOOKLET DAN FLIP CHART TERHADAP PENURUNAN SKOR OHI-S SISWA SD AL-IKHLASIAH MEDAN - Siska ella natassa; Darmayanti Siregar (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Poor dental cleaning habits can lead to plaque accumulation. One of the ways to remove plaque is by brushing your teeth. The plaque will appear within one to two days if there are no oral hygiene measures. The lack of motivation on children in maintaining dental hygiene is caused by various factors such as knowledge and behavior in maintaining dental health. Health education for children is usually carried out through preventive and promotive efforts, one of which is Dental Health Education (DHE) as a form of health education. Booklet and flip chart media are usually used in giving health information because they are effective, easier in making, and can be carried everywhere. The purpose of this study was to determine the effectiveness of DHE using the booklet and flip chart media to reduce the OHI-S scores before, a week, and a month after counseling is being given. Methods: This study is true experimental research with one group pre-test post-test design. Sampling using random sampling method and were statistically analyzed by using Wilcoxon and Mann Whitney test. Results: The results showed a significant difference in the mean score of OHI-S between the booklet and flipchart groups before, after a week, and after a month (p = 0.001) and (p = 0.0001). Conclusion: DHE using flipchart media is more effective in reducing children's OHI-S scores rather than a booklet